Picolinate-mediated immunomodulation: insights from Mendelian randomization on the role of NK cell percentage in the pathogenesis of lichen planus - Cao, Jianye; Du, Tiantao; Li, Jian; Chen, Baiyu; Xie, Xianting; Zhang, Guoshu; Feng, Jia; Xu, Tao (Frontiers in Immunology, 2024)
BackgroundLichen planus (LP), an autoimmune disorder, remains incompletely understood in terms of its etiological mechanisms. This study aims to elucidate causal relationships among immune cell populations, plasma metabolites, and lichen planus using Mendelian randomization (MR) techniques.MethodsEmploying a two-sample, two-step MR approach, with single nucleotide polymorphisms (SNP) serving as genetic instruments for both exposures and mediators, this study minimizes biases from confounding and reverse causality. Leveraging summary statistics from genome-wide association studies (GWAS) involving 731 immune cell traits (N = 3757), 1091 plasma metabolite traits (N = 8299), and lichen planus (N = 367668), inverse variance weighting (IVW) is adopted as the primary MR analytical method. The total effect of immune cells traits on LP is decomposed into direct and indirect effects mediated by plasma metabolites.ResultsMR analysis reveals causal associations for 28 immune cell traits and 38 plasma metabolites with LP (PIVW < 0.05). Specifically, NK % lymphocyte shows a negatively correlated causal effect with LP (ORIVW = 0.952; 95% CI: [0.910, 0.995], PIVW= 0.030). Among mediators, Picolinate significantly contributes, explaining 16.4% (95% CI: [28.3%, 4.54%]) of the association between NK % lymphocyte and LP.ConclusionThese findings support a potential protective causal effect of NK % lymphocyte on LP, partially mediated by Picolinate levels. Thus, interventions targeting Picolinate levels may mitigate LP burden attributed to low NK % lymphocyte counts. This study provides new evidence and insights into the pathogenesis of lichen planus, advancing our understanding of its underlying mechanisms.